Household’s livelihood trajectories in the context of man-made and natural disasters : a case study from Swat, Pakistan - Shah, Aliman (SLU/Dept. of Urban and Rural Development, 2011)
The purpose of this case study is to explore livelihood trajectories in the context of manmade and natural disasters in three villages of Swat district, Pakistan. These three villages were deeply affected by an armed conflict between the Taliban and Pakistan Army from 2006 to 2009 separately by floods in 2010. This research is based on indepth qualitative analysis of 24 households to trace out the changes in household welfare and livelihood security aftermath of armed conflict and floods.